Przygotowanie do zawarcia małżeństwa katolika z protestantem - Dzierżoń, Ginter (Ius Matrimoniale, 2014)
The author of the presented article focused his attention on the issue of preparation for entering marriage between a Catholic and a protestant. He believes that the preparation should not start with the report of canonical-pastoral talks but rather with questions being asked to both parties aimed at identifying their views on the marriage they are willing to contract. First and foremost, the attention of the priest should focus on the conditions included in canon 1125, n. 1-3 ClC. If the parties do not meet these conditions, any preparations for contracting this marriage should be abandoned. Only when the conditions expressed in canon 1125, n. 1-3 CIC are met, the so-called premarital report should be prepared. After that, it should be decided about the number and time of premarital meetings.